Epilepsy with continuous spike-waves during slow wave sleep: a clinical and electroencephalographic study - Délrio F. Silva; Márcia Marques Lima; Luzinete V.A.t. Gonzalez; Odyna J. Lr. Lopez; Renato Anghinah; Edmar Zanoteli; José Geraldo C. lima (Arquivos de Neuro-Psiquiatria)
We report four children with epilepsy with "continuous spike-waves during slow wave sleep" (CSWSS). The main clinical features were partial motor seizures, mental retardation and motor deficit. The EEG findings were characterized by nearly continuous (>85%) diffuse slow spike and wave activity in two patients, and localized to one hemisphere in two other cases during non-REM sleep. The treatment was effective in improving the clinical seizures, but not the EEG pattern. We believe that this epileptic syndrome has been overlooked and routine sleep EEG studies on epileptic children may disclose more cases of CSWSS.